2009
DOI: 10.1073/pnas.0905549106
|View full text |Cite
|
Sign up to set email alerts
|

“Real-time” obstacle avoidance in the absence of primary visual cortex

Abstract: When we reach toward objects, we easily avoid potential obstacles located in the workspace. Previous studies suggest that obstacle avoidance relies on mechanisms in the dorsal visual stream in the posterior parietal cortex. One fundamental question that remains unanswered is where the visual inputs to these dorsal-stream mechanisms are coming from. Here, we provide compelling evidence that these mechanisms can operate in ''real-time'' without direct input from primary visual cortex (V1). In our first experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 39 publications
2
46
5
Order By: Relevance
“…Together with a parallel study in healthy observers [51], this suggests an involvement of the retino-collicular pathway in the processing of unperceived visual information for eye movements. This pathway is also implicated in blindsight studies assessing hand movements–reaching [77] and pointing [78]. …”
Section: Structural and Physiological Bases Underlying Perception-eyementioning
confidence: 99%
“…Together with a parallel study in healthy observers [51], this suggests an involvement of the retino-collicular pathway in the processing of unperceived visual information for eye movements. This pathway is also implicated in blindsight studies assessing hand movements–reaching [77] and pointing [78]. …”
Section: Structural and Physiological Bases Underlying Perception-eyementioning
confidence: 99%
“…As well as compensation to simply shift the field of view to the unaffected side, some work has suggested that saccadic eye movements (Barbur et al, 1988) and obstacle avoidance (Striemer et al, 2009) can be influenced by unseen stimulation within the blind hemifield.…”
Section: Blindsightmentioning
confidence: 99%
“…Even stronger evidence for a sharp dissociation between visuomotor performance and awareness comes from a recent paper by Striemer, Chapman, and Goodale (2009) showing that a patient with a dense hemianopia following an occipital lesion could avoid obstacles placed in his blind field in a reaching task, even though he never reported seeing those obstacles. Given the demonstrated role of dorsal stream mechanisms in the control of obstacle avoidance Schindler et al, 2006), this new work further suggests that those mechanisms can make use of visual inputs that bypass the geniculo-striate pathway.…”
Section: Visual Awarenessmentioning
confidence: 99%
“…Comparable abilities may be found in the perceptual domain, without the corresponding inference that perceptual processing is always unconscious. Goodale and Milner responded by citing another example of action-blindsight (Striemer, Chapman, & Goodale, 2009). While undeniably impressive, this case does not affect our original argument.…”
Section: Visual Awarenessmentioning
confidence: 99%